Magnetic field-induced phase transitions in the antiferromagnet Nd0.6Dy0.4Fe3(BO3)4 - Zvyagina, G.A.; Zhekov, K.R.; Bilych, I.V.; Zvyagin, А.А.; Bludov, A.N.; Pashchenko, V.A.; Gudim, I.А. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Low-temperature studies of elastic and magnetic characteristics of the single crystal Nd0.6Dy0.4Fe3(BO3)4 have been performed. A transition to the antiferromagnetically ordered state of the magnetic subsystem has been manifested in the temperature behavior of the velocity and attenuation of acoustic modes and magnetization. Spin-reorientation phase transitions, which reveal themselves as anomalies in the behavior of elastic and magnetic characteristics of the crystal in the external magnetic field applied along the axis of the trigonal symmetry of the crystal have been discovered. The phase H–T diagram for H || С3 has been constructed.